Effects of Exergaming on Attentional Deficits and Dual-Tasking in Parkinson's Disease - Schaeffer, Eva; Busch, Jan-Hinrich; Roeben, Benjamin; Otterbein, Sascha; Saraykin, Pavel; Leks, Edyta; Liepelt-Scarfone, Inga; Synofzik, Matthis; Elshehabi, Morad; Maetzler, Walter; Hansen, Clint; Andris, Sarah; et al. (Frontiers in Neurology, 2019)
Introduction: Impairment of dual-tasking, as an attention-based primary cognitive dysfunction, is frequently observed in Parkinson’s Disease (PD). The Training-PD study investigated the efficiency of exergaming, as a novel cognitive-motor training approach, to improve attention-based deficits and dual-tasking in PD when compared to healthy controls. Methods: Eighteen PD patients and seventeen matched healthy controls received a six-week home-based training period of exergaming. Treatment effects were monitored using quantitative motor assessment of gait and cognitive testing as baseline and after six weeks of training. Results: At baseline PD patients showed a significantly worse performance in several quantitative motor assessment parameters and in two items of cognitive testing. After six weeks of exergames training, the comparison of normal gait vs. dual-tasking in general showed an improvement of stride length in the PD group, without a gait-condition specific improvement. In the direct comparison of three different gait conditions (normal gait vs. dual-tasking calculating while walking vs. dual-tasking crossing while walking) PD patients showed a significant improvement of stride length under the dual-tasking calculating condition. This corresponded to a significant improvement in one parameter of the D2 attention test. Conclusions: We conclude, that exergaming, as an easy to apply, safe technique, can improve deficits in cognitive-motor dual-tasking and attention in PD.